Proof by Cases/Formulation 2/Forward Implication/Proof 1

From ProofWiki
Jump to navigation Jump to search


$\vdash \paren {\paren {p \implies r} \land \paren {q \implies r} } \implies \paren {\paren {p \lor q} \implies r}$


By the tableau method of natural deduction:

$\vdash \paren {\paren {p \implies r} \land \paren {q \implies r} } \implies \paren {\paren {p \lor q} \implies r} $
Line Pool Formula Rule Depends upon Notes
1 1 $\paren {p \implies r} \land \paren {q \implies r}$ Assumption (None)
2 1 $\paren {p \lor q} \implies r$ Sequent Introduction 1 Proof by Cases: Formulation 1: Forward Implication
3 $\paren {\paren {p \implies r} \land \paren {q \implies r} } \implies \paren {\paren {p \lor q} \implies r}$ Rule of Implication: $\implies \II$ 1 – 2 Assumption 1 has been discharged